RIHA : International Association of Research Institutes in the History of Art - International Association of Research Institutes in the History of Art (2007)
[Dt.:] RIHA ist eine internationale Vereinigung kunsthistorischer Forschungsinsitute, gegründet 1998 in Paris. Ziel ist der wechselseitige Austausch und die gegenseitige Unterstützung, um die internationale Forschung voran zu bringen. Die Web Site infomiert über Aktuelles, sie enthält eine Liste aller beteiligten kunsthistorischen Forschungsinstitute. - [Engl.:] The purpose of RIHA, the International Association of Research Institutes in the History of Art, founded 1998 in Paris, is to promote education and research in art history and related disciplines, to intensify cooperation between the institutes by facilitating the flow of information on scientific and administrative activities as well as the exchange of research findings, and to encourage the institutes to undertake joint projects.